2016
DOI: 10.1038/srep28937
|View full text |Cite
|
Sign up to set email alerts
|

The first characterization of multidrug and toxin extrusion (MATE/SLC47) proteins in zebrafish (Danio rerio)

Abstract: Multidrug and toxin extrusion (MATE) proteins are involved in the extrusion of endogenous compounds and xenobiotics across the plasma membrane. They are conserved from bacteria to mammals, with different numbers of genes within groups. Here, we present the first data on identification and functional characterization of Mate proteins in zebrafish (Danio rerio). Phylogenetic analysis revealed six Mates in teleost fish, annotated as Mate3–8, which form a distinct cluster separated from the tetrapod MATEs/Mates. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…MATEs are a kind of bidirectional transporters that could exclude substrates based on the electroneutral proton(H + )-coupled organic cation exchange, extensively and abundantly expressed on the apical membrane of mammalian organ barriers including that of the intestinal tract, as well as brain, kidney, liver and bile duct, which belong to the SLC47 superfamily. It is a vital efflux transporter in urinary excretion (Lai, 2014;Lončar et al, 2016;Testa and Waterbeemd, 2007). However, Lee et al (2014) reported that MATE 1 promoted the accumulation of intracellular flavonoids in MATE 1 overexpressed cells, and flavonoids uptake decreased by 75% due to the addition of the MATE inhibitor.…”
Section: Influx Transport Of Enterocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…MATEs are a kind of bidirectional transporters that could exclude substrates based on the electroneutral proton(H + )-coupled organic cation exchange, extensively and abundantly expressed on the apical membrane of mammalian organ barriers including that of the intestinal tract, as well as brain, kidney, liver and bile duct, which belong to the SLC47 superfamily. It is a vital efflux transporter in urinary excretion (Lai, 2014;Lončar et al, 2016;Testa and Waterbeemd, 2007). However, Lee et al (2014) reported that MATE 1 promoted the accumulation of intracellular flavonoids in MATE 1 overexpressed cells, and flavonoids uptake decreased by 75% due to the addition of the MATE inhibitor.…”
Section: Influx Transport Of Enterocytesmentioning
confidence: 99%
“…The known absorbability of aglycones via MATE 1 is in decreasing order of quercetin, kaempferol, luteolin, and apigenin, and it shows a higher affinity with flavonoid aglycone than its glycosides. Interestingly, during drug metabolism in the human liver, bile duct, and kidney, MATE 1 mediates the excretion of metabolites from the cell to the extracellular fluids, urine and bile fluids (Lončar et al, 2016). It excludes various organic cationic compounds, such as tetraethylammonium, 1-methyl-4-phenylpyridinium and metformin, and some anionic compounds such as estrone sulfate, acyclovir, and ganciclovir, out of cells (Astorga et al, 2012;Tanihara et al, 2007).…”
Section: Influx Transport Of Enterocytesmentioning
confidence: 99%
“…Furthermore, the data suggest that the role of OATP/Oatp transporters in steroid catabolism could be evolutionarily conserved from fish to mammals. Previously, some selected steroids were shown to interact with Oatp1d1 (Popovic et al 2014(Popovic et al , 2013, but some steroids also interact with zebrafish Oct1 (Mihaljevi c et al 2017) or zebrafish MATE/SLC47 proteins (Lon car et al 2016). Popovic et al (2013Popovic et al ( , 2014 showed that Oatp1d1 serve as a high-affinity transporter for conjugated steroids such as estrone 3-sulfate, estradiol-17-glucuronide, and dehydroepiandrosterone sulfate.…”
Section: Resultsmentioning
confidence: 99%
“…This was especially the case for the membrane pump that denoted multidrug and toxin extrusion protein (MATE), which was expressed more than one hundred times higher in the 2014 perch compared to the 2010 perch. Genes coding for MATE proteins have been characterized in zebrafish (Loncar et al, 2016). Genes for other drug membrane transporters also had a markedly higher mRNA expression in 2014 fish but not to the same extent as for the MATE gene.…”
Section: Membrane Pumps and Detoxificationmentioning
confidence: 99%